Analisis Kritis Atas Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 Dalam Kontek Perlindungan Hak Konstitusonal Warga Negara dan Hak Asasi Manusia - Deltiya Cahayani; Moch Fahmi Faozi; Muhamad Sunan Rizky; Resna Amelia Putri; Shinta Devy Melani (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
In legislative negotiations, the position of the constitutional court is quite high. The constitutional court can change laws that conflict with the constitution by declaring that the law does not have binding legal force. And also the decision of the Constitutional Court is final and binding. So any decision of the constitutional court cannot be contested, even by the MKMK because the decision that has been determined is a permanent decision. So this journal was created to focus on the Constitutional Court decision No.90/PUU-XXI/2023 in the context of Protection of Citizens' Constitutional Rights and Human Rights. This research method is focused on the literature case study method and analysis of previous documents related to the title of this research. Because the Constitutional Court Decision No.90/PUU-XXI/2023 is a quite complex problem for people who do not agree with the decision and question whether the decision can be an effort to protect the constitutional rights of citizenship and human rights.